2017
DOI: 10.1016/j.pjnns.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of l -dopa and DBS-STN on saccadic eye movements in advanced Parkinson's disease

Abstract: This prospective study comparing the influence of l-dopa and DBS-STN on saccades in advanced PD showed contrasting results between these two treatments; the majority of the studied parameters in patients on DBS-STN were similar as in the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 14 publications
4
24
0
Order By: Relevance
“…As most of our patients are in the early-stages of PD, and RBD has been thought to be an effective tool for the early diagnosis of PD, the fact that saccade latency is associated with RBD suggests that saccade latency may be important for early diagnosis of PD. On the other hand, our results indicated that saccade latency is associated with the use of dopamine medicine, which is consistent with previous studies ( 25 , 26 ). These findings suggest that levodopa improves the function of the voluntary frontostriatal system, which is deficient in PD.…”
Section: Discussionsupporting
confidence: 93%
“…As most of our patients are in the early-stages of PD, and RBD has been thought to be an effective tool for the early diagnosis of PD, the fact that saccade latency is associated with RBD suggests that saccade latency may be important for early diagnosis of PD. On the other hand, our results indicated that saccade latency is associated with the use of dopamine medicine, which is consistent with previous studies ( 25 , 26 ). These findings suggest that levodopa improves the function of the voluntary frontostriatal system, which is deficient in PD.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies examining this have produced conflicting results [13] where saccadic parameters have differed not only in degree, but in some cases also in direction. For example, levodopa has been reported as both increasing [14][15][16][17][18] and decreasing [19][20][21] prosaccadic latency. Other reported effects include a reduction in the antisaccadic error rate [22], and improvement of prosaccadic accuracies [23] and amplitudes [24].…”
Section: Introductionmentioning
confidence: 99%
“…There are also studies where DBS fails to produce any effect at all (Schmalbach et al, 2014; Tokushige et al, 2018), and it was even reported to worsen saccadic performance in a study with 12 PD patients and four ET patients (Bangash et al, 2019). Because L‐DOPA seems to have an opposite effect on saccadic eye movements as DBS STN (it improves voluntary saccades, but prolongs latency of visually guided saccades—for more details see the section below, and Table 1) (Dec‐Cwiek et al, 2017), the variability of reported outcomes may relate to differing methodologies (ON or OFF medications) employed. In addition, disease duration and patient age vary considerably across research papers and minor variabilities in DBS electrode placements may also contribute to difference in results (Shaikh et al, 2018).…”
Section: Dbs and Eye Movementsmentioning
confidence: 99%
“…Although all saccades share this final common pathway, differing task demands can result in differential recruitment of higher-level control areas. As with voluntary body movements, voluntary saccades seem to be Fischer et al, 2016;Goelz et al, 2017;Lohnes & Earhart, 2012;Nilsson et al, 2013;Sauleau et al, 2008;Temel et al, 2008;Yugeta et al, 2010Yugeta et al, , 2013 ↑ A ↓ L Gpi DBS (Antoniades et al, 2015;Fridley et al, 2013) No eff VIM DBS (Kronenbuerger et al, 2010) ↓ L STN DBS Sauleau et al, 2008, Temel et al, 2008, Yugeta et al, 2010, Lohnes & Earhart, 2012, Nilsson et al, 2013, Yugeta et al, 2013, Fischer et al, 2016, Dec-Cwiek et al, 2017, Goelz et al, 2017 (Fujiwara et al, 2017) No eff R STN DBS…”
Section: Saccadesmentioning
confidence: 99%
See 1 more Smart Citation